From surface to seabed Journey to becoming underwater welder - Siti Rabiatull Aisha, Idris (UMPSA, 2024)
KUANTAN, 22 April 2024 – Final year students from six institutions including higher education institutions (IPT), colleges and polytechnics across the country who have not yet found employment, recently participated in the Introduction to Underwater Welding Programme.